Is Religious Self-Regulation a Risk or Protective Factor for Men’s Intimate Partner Violence Perpetration? - Davis, Rachel E. (Journal of interpersonal violence, 2022)
Recent research has indicated that religiosity has multiple dimensions and that religious self-regulation may be a more effective predictor of intimate partner violence (IPV) perpetration than other measures of religiosity, such as frequency of prayer or church attendance. Nonetheless, studies have produced inconsistent results regarding the associations between religious self-regulation and IPV perpetration. Moreover, no studies have included self-reported level of religiosity in addition to religious self-regulation in predictive models of IPV perpetration. The present study sought to address the following research question: What is the association between religious self-regulation and men?s IPV perpetration, accounting for self-reported level of religiosity? A convenience sample of 289 men, who had been in their current committed heterosexual relationship for at least one year, were recruited via Amazon?s Mechanical Turk and responded to an online survey. Logistic and negative binomial regression analyses indicated that introjected religious self-regulation was significantly positively associated with physical, psychological, and sexual IPV perpetration, while identified religious self-regulation was significantly negatively associated with physical, psychological, and sexual IPV perpetration, supporting both hypotheses. These findings have implications for faith leaders and secular service providers seeking to develop effective, culturally sensitive, and empirically informed IPV intervention and prevention strategies.